Tribal development since independence - Chaudhary, S.N. (ed.) (New Delhi Concept, 2008)
Book Summary of Tribal Development Since Independence This book, containing 19 papers, presented at a national seminar, organized by the Rajiv Gandhi Chair in Contemporary Studies, Barkatullah University, Bhopal, attempts to take Stock of the status of tribal development in India since independence. Analyzing socio-economic implications of both Institutional and voluntary interventions for tribal development, the contributors address issues concerning social exclusion, marginalizing, watershed approach for socio-economic development of tribal, impact of globalization, socio-ecological changes and tribal livelihood options, tribal communities' participation in Panchayati Raj Institutions, and Civil Society Initiatives to support Tribes for Capital building through microfinance. About the Author S.N. Chaudhary , Professor of Sociology, is currently Rajiv Gandhi Chair Professor at Barkatullah University, Bhopal. He is a former fellow of A.N. Sinha Institute, Patna, Indian Institute of Advanced Study, Shimla and SMH, Paris. He has conducted fieldwork among Red Indians in Canada. He has completed and edited 23 Books and published 50 Research articles. He has produced 23 Ph. Ds. Currently he is working on Tribal Development, Tribal Indebtedness, Primitive Tribe and Impact of Technology on Society.
Keywords: India-Scheduled tribes-Social conditions-Congresses